IDENTIFYING INDIVIDUAL SPECIMENS AMONG SPECIES USING COMPUTER VISION - Mr. Aakash Ravindra Shinde; Ms. Praneeta Gopal Dumbre; Ms. Ruchira Kailas Borkar; Mr. Kshitij Hemant Patil; Dr. Amol V. Dhumane (International Journal of Innovations in Engineering Research and Technology, 2021)
Earth provides shelter to more than 8.7 million species, when confronted with accelerating extinction rates of species during the last half of this century concerns for conservation of this ecological cycle is of utmost importance. Several methods are used for conservation of species and gather data for their sustenance, most of these methods utilises direct contact with the individual for their surveillance this results in a tedious process of handling the specimen and mounting devices on the individual and also causes these devices to stay on the individuals even after the devices are unable to function. Computer Vision and Artificial intelligence has shown promising results for the last decade for systems like facial recognition, object detection, etc. Camera trap methods were used to for tracking animals in a designated area but they rarely provide information about individual animal. We in this manuscript provide with a solution using Computer Vision for determining individual specimen among several species.